Frost rings in 1627 BC and AD 536 in subfossil pinewood from Finnish Lapland - Helama, Samuli; Saranpää, Pekka; Pearson, Charlotte L.; Arppe, Laura; Holopainen, Jari; Mäkinen, Harri; Mielikäinen, Kari; Nöjd, Pekka; Sutinen, Raimo; Taavitsainen, Jussi-Pekka; Timonen, Mauri; Uusitalo, Joonas; et al.
2019